Corrosion characteristics of heat-treated biomedical grade 316L stainless steel in simulated body fluids - Ngeleshi Michel Kibambe; Babatunde Abiodun Obadele; Bukola Joseph Babalola; Ufoma Silas Anamu; Peter Apata Olubambi (Results in Materials)
In this study, we investigated the corrosion behaviour of heat-treated biomedical grade 316L Stainless Steel (SS 316L) in simulated body fluids. SS 316L is widely used in biomedical applications due to its excellent mechanical properties and biocompatibility. Nonetheless, concerns about its susceptibility to corrosion in physiological environments persist. To mitigate these concerns, heat treatment was employed to enhance the material's corrosion resistance by modifying its microstructure. Specimens underwent heat treatment at varying temperatures (1050–1200 °C) for 1 h, followed by rapid water cooling. The corrosion behaviour of both untreated and heat-treated samples was assessed using electrochemical techniques, including potentiodynamic polarization and electrochemical impedance spectroscopy, in simulated body fluids with 0.9 % NaCl. The specimen exhibiting optimal corrosion resistance in this solution was further evaluated in Hanks Balanced Salt Solution enriched with Mg2+ and Ca2+ ions (HBSS+). The results highlighted that the specimen subjected to heat treatment at 1200 °C, followed by water quenching (HT1200 °C/1hr/WQ), experienced deterioration due to galvanic effects between the γ-austenite and δ-ferrite phases. Conversely, the specimen heat-treated at 1100 °C, followed by water quenching (HT1100 °C/1hr/WQ), demonstrated the highest corrosion resistance in 0.9 % NaCl, even surpassing the untreated sample. This improved corrosion resistance was attributed to the combination of moderate and uniform grain size and complete transformation to the austenitic phase during heat treatment. However, when the (HT1100 °C/1hr/WQ) specimen was immersed in a more aggressive HBSS+ solution, its corrosion resistance deteriorated, suggesting the influence of the medium despite microstructural improvement.